An Investigation of Teachers’ Attitudes towards the Utility of Digital Games in the Social Studies Courses: Ayşe ALTUN, Erhan GÖRMEZ (PJDOL, 2023)
The aim of this study was to determine the attitudes of teachers towards using digital games in social studies courses. The sample of the study was consisted of social studies teachers and primary school teachers who attend social studies course in secondary schools affiliated to Van District National Education Directorate. Total 192 teachers voluntarily participated in the study. In the study, the Digital Games Utilization Scale (DGUS) was used to collect quantitative data.